Broad Repertoire of the CD4+ Th Cell Response in Spontaneously Controlled Hepatitis C Virus Infection Includes Dominant and Highly Promiscuous Epitopes - Schulze zur Wiesch, Julian; Lauer, Georg M; Day, Cheryl L; Kim, Arthur Y; Ouchi, Kei; Duncan, Jared E; Wurcel, Alysse G; Timm, Joerg; Jones, Andrea M; Mothe, Bianca; Allen, Todd M; McGovern, Barbara; et al. (The Journal of immunology (1950), 2005)
A vigorous hepatitis C virus (HCV)-specific Th cell response is regarded as essential to the immunological control of HCV viremia. The aim of this study was to comprehensively define the breadth and specificity of dominant HCV-specific CD4+ T cell epitopes in large cohorts of subjects with chronic and spontaneously resolved HCV viremia. Following in vitro stimulation of PBMC, HCV-specific cell cultures from each subject were screened with an overlapping panel of synthetic 20-mer peptides spanning the entire HCV polyprotein. Of 22 subjects who spontaneously controlled HCV viremia, all recognized at least one of a group of six epitopes situated within the nonstructural (NS) proteins NS3, NS4, and NS5, each of which was detected by >30% of subjects, but most subjects recognized additional, more heterogeneous specificities. In contrast, none of the most frequently targeted epitopes was detected by >5% of persons with chronic infection. The most frequently recognized peptides showed promiscuous binding to multiple HLA-DR molecules in in vitro binding assays and were restricted by different HLA-DR molecules in functional assays in different persons. These data demonstrate that predominant CD4+ T cell epitopes in persons with resolved HCV infection are preferentially located in the nonstructural proteins and are immunogenic in the context of multiple class II molecules. This comprehensive characterization of CD4+ T cell epitopes in resolved HCV infection provides important information to facilitate studies of immunopathogenesis and HCV vaccine design and evaluation.